Stability check of doubly fed induction generator (DFIG) micro grid power system - Ameerul A. J. Jeman; Naeem M. S. Hannoon; Nabil Hidayat; Mohamed M. H. Adam; Ismail Musirin; Vijayakumar V. (Bulletin of Electrical Engineering and Informatics, 2019)
As of late, expanding interest of renewable energy and consumption of non-renewable energy source have prompted developing advancement of renewable energy technology, for example, wind energy. Wind energy has turned out to be one of the reliable sources of renewable energy, which requests extra transmission capacity and better methods for sustaining system reliability. As of now, doubly fed induction generator wind turbine is the most well-known wind turbine. This paper focuses on DFIG wind farm design using MATLAB/SIMULINK and also investigates the issues of the system stability of the DFIG wind turbine micro grid power system. This analysis includes the changes of voltage, current, real power and reactive power based on various conditions of the power system.